Unveiling the microstructure evolution and mechanical properties in a gas tungsten arc-welded Fe–Mn–Si–Cr–Ni shape memory alloy - Lopes, J. G. (2024)
Fe–Mn–Si–Cr–Ni shape memory alloys (SMAs) are unique low-cost materials with shape memory properties that grant them the ability to be used in both functional and structural applications. Such SMAs are especially sought in the construction sector for the creation of new components and/or the reinforcement of damaged ones. In this study, a Fe–17Mn–5Si–10Cr–4Ni–1(V, C) wt% SMA was gas tungsten arc welded, with the objective to investigate the microstructure and mechanical performance changes occurring after welding. A comprehensive assessment of processing, microstructure and properties relationships was established combining microscopy (optical and electron), synchrotron X-ray diffraction, microhardness mapping and tensile testing including cycling assessment of the joint’s functional performance. It is shown that the present SMA has good weldability, with the joints reaching nearly 883 MPa at fracture strain of 23.6 ± 2.1%. Alongside this, several microstructure differences were encountered between the as-received and as-welded condition, including the formation of ferrite and Fe5Ni3Si2 P213 cubic precipitates amidst the fusion zone in the latter region. Graphical abstract: (Figure presented.)